PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE QUESTIONS STUDENTS HAVE (QSH) DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPNEGERI 2SUNGAI AUR KABUPATEN PASAMAN BARAT - Putri, Sri Kurnia; Aima, Zulfitri; Pratiwi, Merina (Pendidikan Matematika, 2013)
Comprehension of mathematical concept for students is still low becomes a basic of this research. The purpose of this research is to know the comprehension of mathematical concept for active learning strategyâs students type Questions Students Have (QSH) with Handout were better than implementation of conventional learningâs students for grade VIII SMP Negeri 2 Sungai Aur Province of West Pasaman. The type of this research is experimental research by using random planning focused on subject. The populations are students in grade VIII SMP Negeri 2 Sungai Aur Province of West Pasaman, which consist of two classes. Moreover, sample of this research is taken by random, VIII.1 is for experimental class and VIII.2is for control class. The instrument of this research is the comprehension of mathematical concept test. The techniques of data analysis is using t test for one group by software MINITAB is got P-value smaller thanÂ  , so this hyphothesis is accepted. In conclusion, the comprehension of mathematical concept for active learning strategyâs students type Questions Students Have (QSH) with Handout were better than implemented conventional learningâs students for grade VIII SMP Negeri 2 Sungai Aur Province of West Pasaman.